Immunohistochemical expression of HER-2/NEU-CERBB-2 in patients with adenocarcinoma of the stomach - Cirne-Lima,Fernando K (2009)
OBJECTIVES: To determine the prevalence of Her-2/Neu-cerbb-2 in the gastric mucosa of patients with gastric adenocarcinoma in a brazilian patient group. METHODS: The immunohistochemical expression of Her-2/Neu was studied in 37 formalin-fixed paraffin-embedded tissue sections. RESULTS: The immunohistochemical reaction produced by the anti-HER-2/Neu antibody was positive in two cases (5.4%). CONCLUSION: The low prevalence of Her-2/Neu observed in these southern brazilian cases is probably due to the great number of poorly differentiated cancers in this serie.